2014
DOI: 10.1016/j.molcel.2014.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA TARID Directs Demethylation and Activation of the Tumor Suppressor TCF21 via GADD45A

Abstract: DNA methylation is a dynamic and reversible process that governs gene expression during development and disease. Several examples of active DNA demethylation have been documented, involving genome-wide and gene-specific DNA demethylation. How demethylating enzymes are targeted to specific genomic loci remains largely unknown. We show that an antisense lncRNA, termed TARID (for TCF21 antisense RNA inducing demethylation), activates TCF21 expression by inducing promoter demethylation. TARID interacts with both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
220
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(230 citation statements)
references
References 40 publications
4
220
1
5
Order By: Relevance
“…LncRNAs are known to associate with many histone-or DNA-modifying enzymes, including Polycomb Repressive Complex (PRC), 25 MLL/TrxG complex, 26 histone demethylase LSD1, 27 DNA methyltransferase DNMT1, 28 and DNA demethylation regulator GADD45a. 29 Although the detailed biochemical mechanisms remain to be determined, lncRNAs may act through 2 different mechanisms to covalently modulate chromatin. First, lncRNAs can directly bind to chromatin-modifying enzymes, thus serving as a guide to anchor chromatin modifiers to targeted genomic regions or functioning as a decoy to sequester chromatin modifiers from specific genomic sites.…”
Section: Lncrnas As Partners Of Chromatinmodifying Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are known to associate with many histone-or DNA-modifying enzymes, including Polycomb Repressive Complex (PRC), 25 MLL/TrxG complex, 26 histone demethylase LSD1, 27 DNA methyltransferase DNMT1, 28 and DNA demethylation regulator GADD45a. 29 Although the detailed biochemical mechanisms remain to be determined, lncRNAs may act through 2 different mechanisms to covalently modulate chromatin. First, lncRNAs can directly bind to chromatin-modifying enzymes, thus serving as a guide to anchor chromatin modifiers to targeted genomic regions or functioning as a decoy to sequester chromatin modifiers from specific genomic sites.…”
Section: Lncrnas As Partners Of Chromatinmodifying Enzymesmentioning
confidence: 99%
“…A recent study showed that the lncRNA TARID (TCF21 antisense RNA inducing demethylation) acts by coupling with GADD45A to direct the DNA demethylation machinery to specific gene loci in cancer cells to regulate gene expression. 29 Second, lncRNAs can be incorporated into the chromatin-modifying complex and function as part of the complex or as a scaffold to assemble the complex for chromatin modification. In the fruit fly, for example, the lncRNA roX2, after being structurally remodeled by an RNA helicase MLE1, 30,31 becomes incorporated into the male-specific lethal (MSL) protein complex, which then recruits a histone acetyltransferase (MOF) to induce histone acetylation and activate gene transcription in the male X chromosome.…”
Section: Lncrnas As Partners Of Chromatinmodifying Enzymesmentioning
confidence: 99%
“…Apart from TFs, TET-interacting proteins can also recruit it to a particular locus. For instance, Growth Arrest And DNA Damage Inducible Alpha (GADD45A) is a demethylating complex protein that recruits TET to promoter of TCF21, a tumor suppressor found to be hypermethylated in cancer cell lines [116]. PRC2, which is involved in repression of gene expression through Enhancer of Zeste Homolog 2 (EZH2), specifically recruits TET1 by Suppressor of Zeste 12 Protein Homolog (SUZ12) to the H3K27 tri-methylated locus and enriches 5hmC.…”
Section: -Hydroxymethylcytosine Changes Are Locus-specificmentioning
confidence: 99%
“…Previous reports have shown that lncRNAs have multifunctional roles in modulating embryonic pluripotency, differentiation, development and various diseases, particularly in cancer (11)(12)(13). lncRNAs may be classified according to their mode of action and their functions in cells, including genetic imprinting (14,15), modulating the cancer epigenome (9), serving as molecular decoys (16) and post-transcriptional regulation (10).…”
Section: Introductionmentioning
confidence: 99%
“…A B C during the development of disease (11,32,33). To assess the role of RP5-833A20.1 in the regulation of DNA methylation, the present study assessed the methylation level of the NFIA gene promoter using BSP.…”
mentioning
confidence: 99%